Manufacturing of Organic Waste Shredding Machine - Andriani, Devi; Suhendra, Diky Rahmat; Sutriyatna, Sutriyatna; Yani, Rina Dwi; Pratomo, Tri; Sa'adah, Nurul (Universitas Muhammadiyah Metro, 2025)
Organic waste shredders are designed to speed up waste processing by chopping organic matter into smaller sizes, which in turn makes decomposition processes easier, such as composting or biogas production. The effective design of the shredding mechanism is essential for improving machine efficiency and ensuring optimal engine durability. Some factors that need to be considered in the design of an organic waste shredder include the type and characteristics of organic matter, the shredding mechanism used (such as knives, rollers, or hammer mills), motor power and rotation speed, feeding system, and the resistance of the machine's materials to wear. In addition, aspects of safety, user comfort, and noise and vibration reduction are also important elements in machine design. Choosing the right design based on these factors will allow the machine to operate efficiently, produce consistent shredding results, and accelerate the organic waste processing process, ultimately contributing to better and sustainable waste management. Keywords: Chopping Machine, Organic Waste, Enumerating Mechanism, Decomposition, Machine Design